2018
DOI: 10.1530/jme-17-0165
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary exercise and depression-like behavior in rodents: are we running in the right direction?

Abstract: Acute or chronic exposure to stress can increase the risk to develop major depressive disorder, a severe, recurrent and common psychiatric condition. Depression places an enormous social and financial burden on modern society. Although many depressed patients are treated with antidepressants, their efficacy is only modest, underscoring the necessity to develop clinically effective pharmaceutical or behavioral treatments. Exercise training produces beneficial effects on stress-related mental disorders, indicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 176 publications
3
19
1
Order By: Relevance
“…The VWR induction pattern of NAc ΔFosB observed in this study differs from the induction pattern observed after 28 d of juvenile environmental enrichment or 10 d of a 10% sugar dilution, naturally rewarding conditions that both show equal induction of ΔFosB in D1-and D2-MSNs in the NAc subregions [18]. It should, however, be noted that VWR transiently increases plasma corticosterone levels during the first 3 weeks of VWR and is associated with profound adaptations along the hypothalamic-pituitary-adrenal axis [22,49]. Thus, VWR should be considered a physiological stressor, especially during the initial weeks of VWR.…”
Section: Discussioncontrasting
confidence: 88%
See 4 more Smart Citations
“…The VWR induction pattern of NAc ΔFosB observed in this study differs from the induction pattern observed after 28 d of juvenile environmental enrichment or 10 d of a 10% sugar dilution, naturally rewarding conditions that both show equal induction of ΔFosB in D1-and D2-MSNs in the NAc subregions [18]. It should, however, be noted that VWR transiently increases plasma corticosterone levels during the first 3 weeks of VWR and is associated with profound adaptations along the hypothalamic-pituitary-adrenal axis [22,49]. Thus, VWR should be considered a physiological stressor, especially during the initial weeks of VWR.…”
Section: Discussioncontrasting
confidence: 88%
“…Although both the NAc, as well as ΔFosB have been heavily implicated in stress responses and mood disorders [7], our study is the first attempt to directly link NAc ΔFosB to the pro-resilient effects of VWR. Mechanistic studies in rodents, investigating the antidepressant potential of VWR, have previously indicated the involvement of several brain nuclei, most notably the hippocampus and the basolateral amygdala [22,[44][45][46]. Our findings now add the NAc to the brain circuitry involved in the beneficial effects of VWR on stress-related behavior.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations